Traditional Chinese medicine nursing rounds based on integration of medical care model for a patient with severe acute biliary pancreatitis (1例重症急性胆源性胰腺炎患者的医护一体化中医护理查房案例) - ZHENG Naihua (郑乃花); WANG Jiamin (王佳敏); LI Ye (李野); E Haiyan (鄂海燕); WU Zhisong (吴志松); LI Jinxia (李金霞); LIU Dehao (刘德豪); XIANG Wensheng (相文胜); YANG Dongmei (杨冬梅); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
To summarize the practice of Traditional Chinese medicine nursing rounds based on integration of medical care model for a patient with severe acute biliary pancreatitis. Doctors and nurses in charge developed the nursing plan cooperatively, and nurses carried out targeted nursing interventions based on the analysis of disease prognosis, clinical lab examination and clinical symptoms. The nursing rounds based on integration of medical care model was conducive to the recovery of the patient. (本文总结1例重症急性胆源性胰腺炎患者的医护一体化中医护理查房经验。由主管医护共同参与制定护理计划, 实施护理干预措施, 分析患者疾病转归、化验指标以及临床症状改善情况等, 以加快患者排气排便, 促进病情恢复。)